2022
DOI: 10.1021/acsomega.2c04990
|View full text |Cite
|
Sign up to set email alerts
|

Green and Regioselective Approach for the Synthesis of 3-Substituted Indole Based 1,2-Dihydropyridine and Azaxanthone Derivatives as a Potential Lead for SARS-CoV-2 and Delta Plus Mutant Virus: DFT and Docking Studies

Abstract: Great attempts have been done for the development of novel antiviral compounds against SAR-CoV-2 to end this pandemic situation and save human society. Herewith, we have synthesized 3-substituted indole/2-substituted pyrrole 1,2dihydropyridine and azaxanthone scaffolds using simple, commercially available starting materials in a one-pot, green, and regioselective manner. Further, the regioselectivity of product formation was confirmed by various studies such as controlled experiments, density functional theory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…A series of 3-substituted indole-based 1.2-dihydropyridine hybrids were synthesized by Jayabal et al, 95 and their inhibitory potential against SARS-CoV-2 was tested using a molecular docking approach. Out of the 20 prepared derivatives, compound 64 showed good binding affinity against the main protease (M pro ) (PDB code: 6LU7) of SARS-CoV-2 with a binding energy score of −8.6kcal/mol, as compared to the control drug remdesivir with a binding energy value of −7.7kcal/mol.…”
Section: In Silico Studies Of Covid-19mentioning
confidence: 99%
“…A series of 3-substituted indole-based 1.2-dihydropyridine hybrids were synthesized by Jayabal et al, 95 and their inhibitory potential against SARS-CoV-2 was tested using a molecular docking approach. Out of the 20 prepared derivatives, compound 64 showed good binding affinity against the main protease (M pro ) (PDB code: 6LU7) of SARS-CoV-2 with a binding energy score of −8.6kcal/mol, as compared to the control drug remdesivir with a binding energy value of −7.7kcal/mol.…”
Section: In Silico Studies Of Covid-19mentioning
confidence: 99%
“…In this section, representative examples of computationally predicted M pro SARS-CoV-2 inhibitors will be highlighted. Jayabal et al reported the synthesis of 3-substituted indoles 23 through a multi-component green synthetic approach via the reaction of nitroketene S , S -acetal, diamine-containing compound, 3-formylchromone, and indole in the presence of In(OTf) 3 as a catalyst in refluxing ethanol [ 62 ] ( Scheme 12 ). Computationally, some of the synthesized agents ( K1 – K6 ) showed inhibitory properties for SARS-COV-2 M pro (PDB: 6LU7) and spike glycoprotein (PDB: 7NX7) utilizing Auto Dock-Vina software (v. 1.1.2).…”
Section: In Silico Predicted Anti-sars-cov-2 Indolesmentioning
confidence: 99%
“…Computationally, some of the synthesized agents ( K1 – K6 ) showed inhibitory properties for SARS-COV-2 M pro (PDB: 6LU7) and spike glycoprotein (PDB: 7NX7) utilizing Auto Dock-Vina software (v. 1.1.2). For comparison, Remdesivir binding energy = −7.7, −6.5 kcal/mol is against main protease 6LU7 and spike glycoprotein 7NX7, respectively [ 62 ] ( Figure 23 and Figure 24 ).…”
Section: In Silico Predicted Anti-sars-cov-2 Indolesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several waves of SARS-CoV-2 mutants were observed, namely: Alpha (B.1.1.7), Beta (B.1.351), Gamma (P.1), Delta (B.1.617.2), Epsilon (B.1.427 and B.1.429), Eta (B.1.525), Iota (B.1.526), Kappa (B.1.617.1), Mu (B.1.621, B.1.621.1) and Zeta (P.2). The Omicron (B.1.1.529) variant was first identified in Botswana in Nov. 2021 and rapidly spread to all countries worldwide [ [9] , [10] , [11] , [12] ]. The Omicron variant is highly efficiently transmitted between humans.…”
Section: Introductionmentioning
confidence: 99%